SHEPHERDS KEEPING WATCH BY NIGHT (LUKE 2:8) - Dany Christopher (Jurnal Amanat Agung, 2016)
That the birth of Jesus is not commonly associated with the Passover is hardly surprising. There seems to be no Passover allusion, let alone clear citation in this text. However, a closer look suggests that Luke might already evoke the Passover motif in the nativity scene, through his depiction of the shepherds. While therehave been many suggestions regarding the significance of the shepherds in the birth narrative, all those proposals focus mainly on the question of identity (i.e. what the term ‘shepherd’ might evoke). In this paper, I argue that the focus on the temporal setting as well as the action of the shepherds could shed some light to the depiction of the shepherds in the nativity scene. The night setting recalls the Passover night rescue recorded in Exodus 12. Furthermore, keeping watch by night in anticipation of God’s salvation is also a well known motif in the story of Passover, a motif that the Lukan shepherds exemplify. To support my proposal, I will look into several early Jewish writings associating the Passover with nocturnal salvation.